Impact of perception, attitude, and behavior on cyber resilience towards online fraud threats among IIUM students - Jamalludin, Nur Hafifah; Wok, Saodah; Tengku Azzman, Tengku Siti Aisha; Sedu, Nerawi (Pusat Kajian Media & Komunikasi, Fakulti Sains Sosial & Kemanusiaan, UKM, 2023)
Cyber resilience is crucial in facing the rising number of online fraud threats, especially among students, as they are active users of the online platforms. The platforms used for academic purposes and daily activities include online payment transactions or e-banking. Their active usage of online platforms makes them vulnerable to online fraud threats imposed by perpetrators. Developing cyber resilience will help them prepare for, adapt to, and recover from online fraud threats. In explaining the impact of perception, attitude, and behavior on cyber resilience towards online fraud threats among International Islamic University Malaysia (IIUM) students, this study utilizes social exchange theory (SET). SET helps provide an understanding of students’ ability to keep their data secure and seek rewards for long-term benefits such as gaining extra-knowledge on cyber-security as part of their preparation to handle stressful events imposed by perpetrators. The conceptual framework also assumes that during a stressful event imposed by perpetrators, students are likely to be more alert of the risk of becoming victims of online fraud. A quantitative research design was employed in this study. The survey method was used, with questionnaire as the instrument for data collection. A total of 269 undergraduate students from seven different Kulliyyah participated in this study. Findings show that there are significant relationships between perception, attitude, behavior, and cyber resilience towards online fraud. Thus, SET is supported in the study.